Penggunaan Media Kalender Dan Jam Analog Untuk Meningkatkan Hasil Belajar Matematika Tentang Waktu Pada Siswa Kelas III SD Negeri 09 2x11 Enam Lingkung - ., Dedi Mardianto (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Mathematics learning activities in elementary schools must be adapted to the daily lives of students. Mathematics learning that is not related to students' lives will be felt to be less meaningful and less interesting. Learning mathematics requires abstract thinking, one of which is the material of measuring time. Based on interviews with class III teachers, time units are material that is difficult for students to understand. This can be seen from the results of students'daily tests regarding time units (year, week, day and hour) showing that of the 21 students who got a KKM score of 75 only 9 students while the others still did not meet the KKM. This means that 42.88% of students achieved the KKM score. This is because in conveying the concept of a unit of time, the teacher uses the lecture method. The purpose of this research is to improve the results of learning mathematics about units of time through the use of calendar media and analog clocks for class III SD N 09 2X11 Enam Lingkung. This type of research is classroom action research (CAR). The subjects in this remedial research were class III students with 21 students. The data in this study consisted of quantitative data which were analyzed using quantitative analysis techniques with simple statistics in the form of average values and percentages. Based on the results of learning corrective actions that have been carried out, the conclusion of this study is that the application of calendar media and analog clocks can improve mathematics learning outcomes in class III SD N 09 2X11 Enam Lingkung carried out through 2 cycles. The application of calendar media and analog clocks can improve student learning outcomes in mathematics in class III SD N 09 2X11 Enam Lingkung . This is evidenced from the percentage in the initial conditions (pre-cycle) there were 42.86% of students who passed (above the KKM that had been set). After that there was an increase in learning outcomes in cycle I where there were 57.14% of students who had completed and in cycle II learning improvement actions there were 80.95% of students who had completed learning mathematics using the calendar and analog clock media.